2021
DOI: 10.29252/aassjournal.976
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Natural Products and Minerals in the SARS-CoV-2 Pandemic: An Update

Abstract: Coronavirus-disease 19 (COVID-19) has rapidly become a global public health issue, and there is a desperate need for strategies of prevention, reduction, and treatment to halt the epidemic. The coronavirus affects the immune system, and individuals with a compromised immune system, such as those with diabetes, hypertension, obesity, are more susceptible to this virus. Lifestyle-related variables such as physical activity and nutritional supplements can decrease inflammatory markers, increase anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 165 publications
0
1
0
Order By: Relevance
“…Some believe that Pare-siavashan has a protective effect against Covid-19 as a result of strengthening the immune system, and this effect is probably exerted through the inhibition of free radicals and anti-inflammatory effects. 54 In a review study, Tajadini et al studied the strategies to control common symptoms of Covid-19 from the perspective of Iranian medicine. They found that the consumption of Glycyrrhiza glabra, Ficus carica, Cordia myxa, Echium amoenum, and Adiantum capillus veneris was effective in relieving dyspnea.…”
Section: Efficacy Of Adiantum Capillus Veneris Linn In Chemically Ind...mentioning
confidence: 99%
“…Some believe that Pare-siavashan has a protective effect against Covid-19 as a result of strengthening the immune system, and this effect is probably exerted through the inhibition of free radicals and anti-inflammatory effects. 54 In a review study, Tajadini et al studied the strategies to control common symptoms of Covid-19 from the perspective of Iranian medicine. They found that the consumption of Glycyrrhiza glabra, Ficus carica, Cordia myxa, Echium amoenum, and Adiantum capillus veneris was effective in relieving dyspnea.…”
Section: Efficacy Of Adiantum Capillus Veneris Linn In Chemically Ind...mentioning
confidence: 99%
“…It is native to Asia, Europe, America, and Africa and has been used as a perfume and food seasoning since ancient times (89). According to several studies of this well-known medicinal plant, thyme has several pharmacological activities such as anti-viral, antibacterial, anti-inflammatory, anti-oxidant, antidiabetic, anticancer, anti-spasmodic, antiseptic, and anti-cough activities and performance enhancement in the immune system (90,91). Thymol and carvacrol are thyme's main components (92).…”
Section: Thymus Vulgarismentioning
confidence: 99%
“…The overall evaluation of nutritional biochemical indexes in hospitalized outcomes analysis of COVID-19 based on cytokine and mononuclear cells analysis, as well as its value as a guideline for nutritional therapy has been reported. In the current study, with the help of clinical resources in our hospital, we are trying to continue to further clarify the relationship between patients' nutrient status with their corresponding immunity, and highlight the effects of nutrients supplements on the immune system and their possible benefits in combating the harms caused by infection with the COVID-19 virus [13]. At last, univariate and multivariate ordered logistic regression were performed to evaluate which nutrient related factors were important for COVID patient outcome.…”
Section: Introductionmentioning
confidence: 99%